2021
DOI: 10.1039/d1ew00093d
|View full text |Cite
|
Sign up to set email alerts
|

Start-up of bench-scale biofilters for manganese removal under tropical conditions: a comparative study using virgin pumice, silica sand, and anthracite filter media

Abstract: Biofiltration for Mn removal has not been proven in the tropics (18-29°C). Also, the use of pumice as alternative filter media for Mn removal is still poorly known. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, other studies have shown that microbial communities inhabiting the water column can adapt to temperature changes without affecting their growth rate (Zeikus & Brock, 1972). A more recent study showed that water temperature did not affect the start‐up period Mn removal in a bench‐scale anthracite biofilter (Araya‐Obando et al, 2021). Bacterial 16S rRNA gene copy abundances in the chlorinated filter media did not significantly change across the study period, rather they positively correlated with the influent 16S rRNA gene copy abundance ( rho = 0.742, p = .025, Spearman rank correlation).…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies have shown that microbial communities inhabiting the water column can adapt to temperature changes without affecting their growth rate (Zeikus & Brock, 1972). A more recent study showed that water temperature did not affect the start‐up period Mn removal in a bench‐scale anthracite biofilter (Araya‐Obando et al, 2021). Bacterial 16S rRNA gene copy abundances in the chlorinated filter media did not significantly change across the study period, rather they positively correlated with the influent 16S rRNA gene copy abundance ( rho = 0.742, p = .025, Spearman rank correlation).…”
Section: Resultsmentioning
confidence: 99%